Clinical Features and Risk Factors for Mortality Among Long-term Care Facility Residents Hospitalized Due to COVID-19 in Spain. Issue 4 (9th October 2021) - Ramos-Rincón, José-Manuel; Bernabeu-Wittel, Máximo; Fiteni-Mera, Isabel; López-Sampalo, Almudena; López-Ríos, Carmen; García-Andreu, María-del-Mar; Mancebo-Sevilla, Juan-José; Jiménez-Juan, Carlos; Matía-Sanz, Marta; López-Quirantes, Pablo; Rubio-Rivas, Manuel; Paredes-Ruiz, Diana; et al.
Abstract: Background: COVID-19 severely impacted older adults and long-term care facility (LTCF) residents. Our primary aim was to describe differences in clinical and epidemiological variables, in-hospital management, and outcomes between LTCF residents and community-dwelling older adults hospitalized with COVID-19. The secondary aim was to identify risk factors for mortality due to COVID-19 in hospitalized LTCF residents. Methods: This is a cross-sectional analysis within a retrospective cohort of hospitalized patients ≥75 years with confirmed COVID-19 admitted to 160 Spanish hospitals. Differences between groups and factors associated with mortality among LTCF residents were assessed through comparisons and logistic regression analysis. Results: Of 6 189 patients ≥75 years, 1 185 (19.1%) were LTCF residents and 4 548 (73.5%) were community-dwelling. LTCF residents were older (median: 87.4 vs 82.1 years), mostly female (61.6% vs 43.2%), had more severe functional dependence (47.0% vs 7.8%), more comorbidities (Charlson Comorbidity Index: 6 vs 5), had dementia more often (59.1% vs 14.4%), and had shorter duration of symptoms (median: 3 vs 6 days) than community-dwelling patients (all, p < .001). Mortality risk factors in LTCF residents were severe functional dependence (adjusted odds ratios [aOR]: 1.79; 95% confidence interval [CI]: 1.13–2.83; p = .012), dyspnea (1.66; 1.16–2.39; p = .004), SatO2 < 94% (1.73; 1.27–2.37; p = .001), temperature ≥ 37.8°C (1.62; 1.11–2.38; p = .013); qSOFA index ≥ 2 (1.62; 1.11–2.38; p = .013), bilateral infiltrates (1.98; 1.24–2.98; p < .001), and high C-reactive protein (1.005; 1.003–1.007; p < .001). In-hospital mortality was initially higher among LTCF residents (43.3% vs 39.7%), but lower after adjusting for sex, age, functional dependence, and comorbidities (aOR: 0.74, 95%CI: 0.62–0.87; p < .001). Conclusion: Basal functional status and COVID-19 severity are risk factors of mortality in LTCF residents. The lower adjusted mortality rate in LTCF residents may be explained by earlier identification, treatment, and hospitalization for COVID-19.